Propriedades de concreto sustentável produzido com pó do polimento do porcelanato e resíduo da scheelita - Medeiros, Alisson Gadelha (Universidade Federal Rural do Semi-Árido, 2019)
Several wastes are generated daily, which can be organic and inorganic. These wastes are the result of various anthropic activities and can generate serious environmental impacts. Thus, generation, poor packaging and improper disposal are processes that affect environmental health. Given this context, the construction industry is one of the potential sources of waste generation, especially Construction and Demolition Wastes (CDWs) which, however, may be useful through the use of alternative materials through the use of waste such as waste. raw material for sustainable concrete production and minimizing impacts. This assumption is pertinent, since concrete is the second most consumed compound on the planet, and to meet its demand, cement production as well as the exploitation of sand deposits are activities that influence the environment. In this sense, this research aims at the partial substitution of cement and concrete sand by ceramic industry and mining residues, respectively, Porcelain Polishing Residue (PPR) and Tungsten Mine Waste Mud (TMWM), because PPR can be important in the formation and densification of cementitious matrix through the formation of C-S-H (Hydrated Calcium Silicate), pore refinement by filler effect and pozzolanic activity, in order to improve the microstructure and durability of concrete. As for TMWM, because it has silicon dioxide (SiO2) and calcium oxide (CaO) for the chemical improvement of concrete, and granulometry that when mixed with sand, can provide greater compactness to concrete. To make substitutions possible, PPR processing was performed in order to obtain cement compatible particle size and the optimization between sand substitution by TMWM. Thus, an experimental design was developed for the characterization of the materials used in the search for maximum levels of waste substitution, with the aim of producing sustainable concrete and comparing their properties with conventional reference concrete. For this purpose, fresh and hardened tests (physical and mechanical properties), durability test for chloride ion penetration in accelerated chamber and specific analyzes of: X-Ray Diffractometry, X-Ray Fluorescence, Scanning Electron Microscopy and thermogravimetry. All the tests were performed in the materials used, mainly in the residues, as in the concrete in the ages of 7, 28, 90 and 212 days. Therefore, it was possible to obtain substitution levels of 15% for PPR and 81% for TMWM in sustainable concrete production, and compared to the reference concrete, satisfactory indexes of workability, similar resistance range, lower absorption values and total porosity, higher chloride ions penetration resistance and densified C-S-H microstructure surrounded by hexagonal calcium hydroxide plates. Finally, environmental and economic viability becomes a consequence, as cement is the most costly and environmentally impactful material and sand is one of the most consumed aggregates in the world
Keywords: Sustentabilidade; Impactos ambientais; Beneficiamento; Substituições parciais; Materiais cimentícios; Sustainability; Environmental impacts; Beneficiation; Partials replacements; Cementitious materials; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO